REALITAS BAHASA DALAM POSTULAT SAPIR DAN WHORF - Wuwuh Yunhadi (LINGUA : Jurnal Bahasa, Sastra, dan Pengajarannya, 2016)
In the field of linguistics, Sapir and Whorf claimed that language and culture are closely related.  Language is the reflection of how culture of a community shares.  Sapir and Whorf defined two main functions of language in the community.  First, language will change from the original if the language is used far from the center where the language origins.  This concept is named as language drift.  Second, the characteristics of individuals’ culture are manifested in the language they use. This paper is a brief review on theories of language from Sapir-Whorf that inspires on the development of sociolinguistics and discourse analysis in the era that follows.